Positron emission tomography imaging of CD105 expression with(89) Zr-Df-TRC105 - Hong, Hao (2011)
PURPOSE: High tumor microvessel density (MVD) correlates with poor prognosis in multiple solid tumor types. The clinical gold standard for assessing MVD is CD105 immunohistochemistry on paraffin-embedded tumor specimens. The goal of this study was to develop an (89)Zr-based positron emission tomography (PET) tracer for non-invasive imaging of CD105 expression. METHODS: TRC105, a chimeric anti-CD105 monoclonal antibody, was conjugated to p-isothiocyanatobenzyl-desferrioxamine (Df-Bz-NCS) and labeled with (89)Zr. FACS analysis and microscopy studies were performed to compare the CD105 binding affinity of TRC105 and Df-TRC105. PET imaging, biodistribution, blocking, and ex vivo histology studies were performed on 4T1 murine breast tumor-bearing mice to evaluate the pharmacokinetics and tumor targeting efficacy of (89)Zr-Df-TRC105. Another chimeric antibody, cetuximab, was used as an isotype-matched control. RESULTS: FACS analysis of HUVECs revealed no difference in CD105 binding affinity between TRC105 and Df-TRC105, which was further validated by fluorescence microscopy. (89)Zr-labeling was achieved with high yield and specific activity. Serial PET imaging revealed that the 4T1 tumor uptake of (89)Zr-Df-TRC105 was 6.1 ± 1.2, 14.3 ± 1.2, 12.4 ± 1.5, 7.1 ± 0.9, and 5.2 ± 0.3 %ID/g at 5, 24, 48, 72, and 96 h post-injection respectively (n = 4), higher than all organs starting from 24 h post-injection, which provided excellent tumor contrast. Biodistribution data as measured by gamma counting were consistent with the PET findings. Blocking experiments, control studies with (89)Zr-Df-cetuximab, as well as ex vivo histology all confirmed the in vivo target specificity of (89)Zr-Df-TRC105. CONCLUSION: Herein we report the first successful PET imaging of CD105 expression with (89)Zr as the radiolabel. Rapid, persistent, CD105-specific uptake of (89)Zr-Df-TRC105 in the 4T1 tumor was observed.